Direct Imprinting of Laser Field on Halide Perovskite Single Crystal for Advanced Photonic Applications - Zhizhchenko, A. Y.; Cherepakhin, A. B.; Masharin, M. A.; Pushkarev, A. P.; Kulinich, S. A.; Porfirev, A. P.; Kuchmizhak, A. A.; Makarov, S. V. (Laser & Photonics Reviews, 2021)
Single crystal halide perovskites with microscale dimensions are an emerging class of objects for various advanced photonic and optoelectronic applications. Particularly, defect tolerance and broadband tunability of luminescence make them one of the most prospective candidates to develop microlasers for visible range. However, their post‐processing by standard nanolithography methods face a number of problems related to worsening of their properties, thus making gentle laser processing one of best solutions for perovskite patterning. Here, it is shown that femtosecond laser irradiation of single‐crystal halide perovskite CsPbBr3 allows for its precise and ultraclean ablation fully controlled at subwavelength scale by the intensity and polarization distribution of the complex laser field applied. Indeed, the extremely low thermal conductivity (over 300 times lower than that of silicon) and ultrafast thermalization rate makes it possible to reduce heat‐affected zone and avoid melting layer contribution, while the high refractive index (larger than 2) provides high spatial resolution in case of irradiation of pre‐patterned focusing perovskite nanostructures. These features allow for direct imprinting of the incident laser field at wavelength λ = 515 nm, creating micro‐lens and various light‐emitting metasurfaces with deeply subwavelength spatial resolution (down to λ/7). Femtosecond laser irradiation of single‐crystal halide perovskite CsPbBr3 allows for its precise and ultraclean ablation fully controlled at subwavelength scale by the intensity and polarization distribution of the complex laser field applied. The direct imprinting of the incident laser field results in the creation of micro‐lens and various light‐emitting metasurfaces with deeply subwavelength spatial resolution (down to lambda/7).